(untitled) (Zdravstveni glasnik, 2024)
INTRODUCTION: Continuous static load during computer work results in gradual development of pathological changes in musculature of the upper back, neck, and arms. OBJECTIVE: The aim of this paper was to identify problems in the area of the neck, shoulder area and upper limbs associated with static load on employees working on a computer. METHODS: The study was conducted on 162 workers, aged 20 to 60, in the city of Siroki Brijeg, Bosnia and Herzegovina, during 2011. A questionnaire consisting of parts of two standardized questionnaires: “Workplace Appraisal on the Keyboard” from ergonomics in professional therapy, and a questionnaire for upper limbs from the Maastricht region (MUEQ) have been used. Complaints were sought on at least one problem related to the aforementioned anatomical structures present in a minimum duration of one week over the past 12 months. RESULTS: Out of a total of 162 workers, 110 have or have had problems in the past. The number of hours spent on the computer, the years spent at the workplace, the presence of the symptoms, the location of the same, have a statistical significance. Numerous workers do not have a custom work desk, and many of them have not sought adequate medical assistance. CONCLUSION: Long-lasting static work on the computer can be a predisposing factor for the appearance of certain problems on the structures of the neck, shoulder area and upper limbs. An inadequate desk may also have a negative impact on the problem.